2021
DOI: 10.1002/jev2.12071
|View full text |Cite
|
Sign up to set email alerts
|

Human milk extracellular vesicles target nodes in interconnected signalling pathways that enhance oral epithelial barrier function and dampen immune responses

Abstract: Maternal milk is nature's first functional food. It plays a crucial role in the development of the infant's gastrointestinal (GI) tract and the immune system. Extracellular vesicles (EVs) are a heterogeneous population of lipid bilayer enclosed vesicles released by cells for intercellular communication and are a component of milk. Recently, we discovered that human milk EVs contain a unique proteome compared to other milk components. Here, we show that physiological concentrations of milk EVs support epithelia… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
71
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(71 citation statements)
references
References 62 publications
0
71
0
Order By: Relevance
“…In addition, exosomes released by immature DCs have been proven to induce T cells apoptosis by promoting a tolerant immune response. These exosomes can also balance pro-inflammatory and anti-inflammatory effector T cells by inducing auxiliary T cells to differentiate into regulatory T cells [73], which could be achieved by the action exerted by exosome-transported IL-10, thus inducing a tolerance response [76].…”
Section: Immunomodulationmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, exosomes released by immature DCs have been proven to induce T cells apoptosis by promoting a tolerant immune response. These exosomes can also balance pro-inflammatory and anti-inflammatory effector T cells by inducing auxiliary T cells to differentiate into regulatory T cells [73], which could be achieved by the action exerted by exosome-transported IL-10, thus inducing a tolerance response [76].…”
Section: Immunomodulationmentioning
confidence: 99%
“…For example, some exosomal circular RNAs (circRNAs), found in colostrum, play important biological roles through binding to their respective miRNAs, which promote vascular endothelial growth factor expression and induce proliferation and migration of small intestinal epithelial cells. Breast milk exosomes have also been shown to directly enhance gingival epithelial cell migration through p38 mitogen-activated protein kinases and cytoskeleton remodeling [76]. It has been hypothesized that breast milk extracellular vesicles are involved in the selective inhibition of toll-like receptors 3, 4 and 9 (TLR3, TLR4 and TLR9) through the transport of epidermal growth factor, and, probably, cystatin-B cathepsin inhibitor (CSTB) [76].…”
Section: Mother-to-baby Networkmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, Zonneveld et al. have recently reported that human milk EVs can directly inhibit CD4+ T helper cell activation without inducing tolerance ( 100 ). In experimental arthritis studies, our research group at the Radboudumc found circumstantial evidence for this effect on T cells, as mice treated with bovine mEVs showed a marked reduction in Tbet (Th1) and RORyT (Th17) expression in splenocytes.…”
Section: T Cell Activation and Differentiation By Extracellular Vesiclesmentioning
confidence: 99%
“…Previous studies suggest antipathogenic effects of HM components and that the addition of these bioactive molecules (i.e., HMOs, lactoferrin, immunoglobulins, and milk fat globule membrane FGM, extracellular vesicles) to infant formulas may benefit child health (20,(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36), although the studies usually lack methodological rigor and outcomes were based on a small sample size. The studies on recombinant immunoglobulins and bioactivity in the digestive tract are limited.…”
Section: Early Life Nutrition and Health Outcomes In Later Lifementioning
confidence: 99%